PAY LESS TO SAVE PLANET: GREEN LOAN PARADOX DAN RESISTENSI UMKM TERHADAP PEMBIAYAAN BERKELANJUTAN BERSUBSIDI - Sudiyarti, Nining; Rachman, Rosyidah; Usman, Usman; Sutrisno, Eko (Penerbit Lafadz Jaya, 2025)
This study explores the paradoxical phenomenon where Small and Medium Enterprises (SMEs) in Sumbawa Regency resist subsidized green loan schemes despite their economic advantages. Using qualitative methods including in-depth interviews with 25 SME owners, focus group discussions, and document analysis, this research identifies key factors driving resistance: perceived complexity of application procedures, distrust toward financial institutions, concerns about sustainability requirements as operational burdens, limited environmental awareness, and preference for informal financing networks. The findings reveal a critical gap between policy design and grassroots implementation, where rational economic incentives fail to overcome institutional, cultural, and informational barriers.